Embedding Islamic Business Ethics in MSMEs: Insights from an Indonesian Case Study - Rachmiya Saputri; Muhammad Fahri; Ilham Azra Putra; Dedi Albekri; Muhammad Redho Yulizar (Education and Sociedad Journal, 2024)
This study aims to analyze the application of Islamic business ethics principles in the MSME Sirup Markisaku, a Sharia-based small business located in Lubuklinggau. Islamic business ethics, encompassing principles of honesty, fairness, transparency, and care, are considered essential in MSME operations to ensure business sustainability and foster trust with consumers and partners. This research utilizes a qualitative approach through in-depth interviews with the MSME owner, employees, business partners, and consumers. The findings reveal that Sirup Markisaku has implemented the principle of honesty in product information disclosure, maintaining the quality of raw materials, and ensuring fair pricing for consumers. Additionally, transparency in operations and profit-sharing is practiced to maintain equitable relationships with business partners and employees. However, certain areas still need improvement, such as enhancing transparency in financial reporting and providing further training for employees on Sharia business ethics. This study contributes to the development of Sharia-based MSMEs by offering recommendations on how Islamic business ethics principles can be strengthened and applied more effectively to support business growth and sustainability.